Containment: Exploring the concept of agency in children's statutory encounters with social workers. (February 2019) - Morrison, Fiona; Cree, Viviene; Ruch, Gillian; Winter, Karen Michelle; Hadfield, Mark; Hallett, Sophie
This article examines children's agency in their interactions with social workers during statutory encounters in a child protection context. It draws from a UK-wide ethnographic study. It finds that much of social workers' responses to children's agency in this context are best understood as a form of 'containment'. In doing so, it offers an original and significant contribution to the theoretical understanding of children's agency, as well as its application in social work practice.